POSTTHROMBOPHLEBITIC SYNDROME IN THE PRACTICE OF AN OBSTETRIC (CLINICAL CASE) - Юлия Валерьевна Васютинская; Елена Владимировна Рудаева; Владимир Вячеславович Павленко; Ольга Борисовна Зарубина; Анастасия Александровна Подушко; Данил Викторович Вебер; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Сергей Валерьевич Рыбников; Марина Александровна Каткова; Игорь Анатольевич Зимин; Андрей Владимирович Келлер (The Publishing House Medicine and Enlightenment, 2021)
The incidence of venous thromboembolic complications during pregnancy and the postpartum period is up to 5 cases per 1000 women. Deep vein thrombosis of the lower extremities and associated thromboembolism of the pulmonary artery are a serious problem in modern medicine, complicates the course of the gestational process, posing a threat to the health of women and the fetus, often necessitates surgical interventions, and leads to an increase in maternal and perinatal mortality. Most cases of deep vein thrombosis of the lower extremities are diagnosed in the second half of pregnancy and in the first two weeks of the postpartum period.